2016
DOI: 10.4049/jimmunol.1600307
|View full text |Cite
|
Sign up to set email alerts
|

Multiple IgH Isotypes Including IgD, Subclasses of IgM, and IgY Are Expressed in the Common Ancestors of Modern Birds

Abstract: Although evolutionarily just as ancient as IgM, it has been thought for many years that IgD is not present in birds. Based on the recently sequenced genomes of 48 bird species as well as high-throughput transcriptome sequencing of immune-related tissues, we demonstrate in this work that the ostrich (Struthio camelus) possesses a functional δ gene that encodes a membrane-bound IgD H chain with seven CH domains. Furthermore, δ sequences were clearly identified in many other bird species, demonstrating that the δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…To date, it has been reported that there are three functional μ genes in the crocodilian IgH locus and two in the ostrich and emu, and at least four Squamata species have more than one μ gene [4, 35, 38]. The isotypes mentioned above originated from duplications of the exons that encode for the C μ located at the 5’ end.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been reported that there are three functional μ genes in the crocodilian IgH locus and two in the ostrich and emu, and at least four Squamata species have more than one μ gene [4, 35, 38]. The isotypes mentioned above originated from duplications of the exons that encode for the C μ located at the 5’ end.…”
Section: Discussionmentioning
confidence: 99%
“…Human and mouse also possess certain subclasses of IgG (French and Harrison, 1984) and IgA (Kett et al, 1986), which enable more subtle immune responses. Among those Igs, IgM and IgD are evolutionarily conserved and are thought to be the primordial Ig isotypes (Edholm et al, 2011; Han et al, 2016). However in teleosts, IgM (Bradshaw et al, 1971; Hordvik et al, 2013), IgD (Edholm et al, 2010; Ramirez-Gomez et al, 2012; Wilson et al, 1997) and IgT or IgZ (H chain: τ or ζ) (Hansen et al, 2005; Hu et al, 2010) have been identified in various fish species.…”
Section: Introductionmentioning
confidence: 99%
“…22), which facilitates alternative mRNA splicing of the heavy chain variable (VDJ H ) exon to either IgM or IgD heavy chain constant (C)-region exons. This arrangement is evolutionarily preserved in most species of fish, amphibians, reptiles, birds and mammals1723, yet mice lacking IgD have normal B cell development and only slightly delayed antibody responses2425. Likewise, comparison of mice that express only IgM or only IgD reveals no discernable difference in the capacity of these alternative receptors to promote B cell development, tolerance, activation or antibody secretion in vivo 2627.…”
mentioning
confidence: 99%